An Overview of Organoid and 3-Dimensional Models in Multiple Myeloma. Issue 3 (May 2021) - Rodriguez, Cesar
Abstract : Abstract: Multiple myeloma is a hematological malignancy of differentiated B cells that resides primarily in bone marrow niches. Its interaction with the microenvironment is known to provide a survival advantage and plays an important role in drug resistance. Despite the increased efficacy of new treatment drugs, clinical results oftentimes fall short of in vitro observations, and this disease remains incurable. Conventional 2-dimensional cultures used to perform chemosensitivity assays and the established multiple myeloma cells lines commonly used do not replicate the conditions seen in vivo. This review presents various 3-dimensional culture platforms for myeloma that attempt to overcome this obstacle by incorporating aspects of the tumor microenvironment. The unique features of each model and contributions they have provided in personalized medicine, tumor physiology, and chemosensitivity assays will be summarized.